Manajemen Pemasaran Keripik Nangka (Artocarpus Heterophyllus Lamk) Kayavit di CV. Puri Pangan Lestari - Rahaju, Juli; Rahmawati, Mariana Fitri; Muhandoyo, Muhandoyo; Hariyanto, Annisa Mauliddiyah (AKADEMIK: Jurnal Mahasiswa Ekonomi & Bisnis, 2025)
CV. Puri Pangan Lestari has implemented effective and proper marketing management, which includes five key stages: planning, organizing, execution, controlling, and evaluation. The planning stage involves formulating strategies for marketing Kayavit jackfruit chips, while organizing entails delegating responsibilities among individuals involved in the marketing process. The execution stage ensures the marketing activities align with the planned strategies, controlling focuses on monitoring marketing activities to maintain alignment with the plans, and evaluation identifies challenges and issues encountered during the marketing management process. Consumer purchasing decisions for Kayavit jackfruit chips are influenced by two main factors. First, socio-cultural factors such as recommendations from peers, product availability, needs, and local habits. Second, personal factors, including financial condition, price, lifestyle, taste, past experiences, and the product's appeal. However, the company faces several challenges in its marketing management, including less strategic store locations, limited use of e-commerce platforms, inadequate promotional efforts, and suboptimal employee performance. To address these challenges, the proposed solutions include selecting busier locations, leveraging e-commerce platforms to enhance consumer accessibility, utilizing social media for broader promotion, and implementing stricter work regulations and clearer responsibility assignments for employees. These measures aim to optimize marketing efforts and increase the brand's market reach.